(untitled) (Heritage, 2025)
The Church of St. Nicholas, located in the village of Božica near Bosilegrad, is one of the oldest preserved churches in the regions of Vlаsina and Bosilegradsko Krajište, dating back to the early 17th century. It was built, painted, and equipped with an iconostasis during the first decade of the 17th century, coinciding with the renovation of the Peć Patriarchate, which marked the revitalization of Orthodox Christian life in the Ottoman Empire. In the second half of the 19th century, a more extensive renovation of the church’s interior took place. This renovation involved replacing the original 17th-century iconostasis with a new one that is still preserved today. The creation of the new iconostasis occurred in two phases, in 1867 and 1883, and was produced by two zographs. One of these zographs remains unknown, while the other has been identified as Zaharije Pop Radojkov, a prominent representative of the Samokov Zograph school. Although the church’s modest dimensions limited the size of the iconostasis and the number of icons it could hold, the iconostasis features a complex program that meets liturgical and symbolic requirements, as well as the needs of the local parochial community. Most of the icons on the iconostasis bear donor inscriptions, which today provide rich evidence of the former structure of the local parish community.